Comparison of Ultrasound-Guided Ilioinguinal and Iliohypogastric Nerve Block with and without Tramadol for Postoperative Pain in Patients Undergoing Caesarean Delivery: Ultrasound Ilioinguinal and Iliohypogastric Nerve Block: Tramadol for Caesarean Delivery - Safir, Saad Salman; Khan, Muhammad Yahya Bakhtiar; Ali, Amber; Shafiq, Mohammad; Khan, Fahad (Pakistan Journal of Health Sciences, 2026)
Maternal relief, early mobilization, and breastfeeding are dependent on the effective postoperative pain management following caesarean section. Objectives: To compare the analgesic effect of ultrasound-guided ilioinguinal-iliohypogastric nerve block with ropivacaine only versus ropivacaine with tramadol in patients who underwent elective cesarean delivery. Methods: A retrospective study was performed on a sample of 100 individuals, and the study was performed in two groups. Group A was given ropivacaine, and Group B was given ropivacaine and tramadol to relieve postoperative pain. Median [IQR] and mean ± SD were estimated, and comparisons between them were done by Fisher’s Exact test, Mann-Whitney U-test, and independent t-test, with p≤0.05 taken as significant. Results: The combination of Ropivacaine and Tramadol gave better analgesia in patients who had a caesarean than when Ropivacaine was used. The combination group had a much longer pain-free period (20 vs. 14 hours, p=0.002), and the overall pain scores were lower (1.0 ± 0.7 vs. 1.8 ± 1.0, p=0.001). The patients needed fewer rescue analgesics, and there was no difference in opioid side effects. Conclusions: The combination of Tramadol and Ropivacaine has a significant positive effect on postoperative analgesia in patients undergoing a caesarean section, extending pain-free periods and decreasing the intensity of pain, with minimal adverse effects, which makes it an effective and safe approach to enhancing patient comfort and satisfaction.